Evaluation of the zootechnical additive VITAFERT in the productive performance and health of pre-fattening piglets - Beruvides, A.; Elías, A.; Valiño, E.; Millian, G.; Lezcano, Y.; Moliner, J. L.; Rodríguez, Marlen; Zamora, H. (Cuban Journal of Agricultural Science, 2018)
This study was carried out in the Centro Porcino Gelpis from Matanzas province, in order to evaluate the effect of the zootechnical additive VITAFERT in the productive performance and health of pre-fattening piglets. A completely randomized design, with four treatments, was applied. A total of 200 crossbred pigs were used, which were kept in Flat Decks. Control group received basal diet and the other three treatments were offered different levels of inclusionof Vitafert: G-I: 5 G-II: 10 and G-III: 15mL/kg of liveweight, respectively. Productive and health indicator were evaluated. The use of this additive improved weight gain in the evaluated groups in 0.70, 1.41 and 2.76 kg of liveweight, daily mean gain was 20, 30 and 70 g of liveweight and there was a better performance of food conversion in the G-III. In the three evaluated groups, there was low incidence of diarrheas (2.65 %, 1.58 % and 0.93 %) regarding the control, which was 5.67 %, and there were no deaths in groupsII and III, for P<0.0001. It can be concluded that the addition of the zootechnical additive Vitafert improves the productive performance and health of pre-fattening piglets. Key words: productive indicators, pigs, probiotic, diarrheas